Pulse pressure and age at menopause - Eigenbrodt Marsha; Sharrett A Richey; Luoto Riitta; Arnett Donna (BMC, 2002)
Abstract Background The objective of this study was to study the association of early age at menopause with pulse pressure (PP), a marker of arterial stiffness, and PP change. Methods The effect of natural menopause was studied in 2484 women from the Atherosclerosis Risk in Communities (ARIC) Study who had not used hormone replacement therapy and who had not had a hysterectomy. The cross-sectional association of age with PP was evaluated in the entire cohort. The cross-sectional association of recalled age at menopause was evaluated in the 1688 women who were postmenopausal at baseline. PP change over 6 years was assessed in relation to menopausal age separately in women who were postmenopausal at baseline and in those whose menopause occurred during the 6-year interval. Results Chronological age was strongly and positively associated with PP in cross-sectional analyses, but not independently associated with PP change. While menopausal age was not associated cross-sectionally with PP, early age at menopause (age<45) was significantly and independently associated with a slightly larger increase in PP (8.4, 95% CI 7.0-9.8) than later menopause (6.5, 95% CI 5.8;7.2). However, among normotensive women the difference was not statistically significant (p = 0.07, 6.1 vs 4.7). Conclusions Early age at menopause may be related to a greater increase in arterial stiffness, but the effect appears to be small and further evidence is needed.